2021
DOI: 10.1016/j.jtauto.2021.100091
|View full text |Cite
|
Sign up to set email alerts
|

Latent rheumatic, thyroid and phospholipid autoimmunity in hospitalized patients with COVID-19

Abstract: Autoimmune responses mediated by autoantibodies have been previously observed in SARS-CoV-2 infection. Herein, we evaluated the presence of rheumatic, thyroid and phospholipid autoantibodies in sera samples from 120 hospitalized patients with COVID-19 in comparison to pre-pandemic samples from 100 healthy individuals. In addition, to estimate the frequency of these autoantibodies in COVID-19, a meta-analysis of selected articles was conducted. Hospitalized patients with COVID-19 displayed latent autoimmunity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 28 publications
(37 reference statements)
2
53
2
2
Order By: Relevance
“…However, clinical studies showed contradictory results. In one study, increased TPOAb positivity was detected [ 24 ], while increased autoimmunity was not detected in others [ 9 , 12 ]. In the light of this knowledge, we evaluated the TPOAb and TGAb in 205 patients, but we could not observe an increased rate of antibody positivity according to the normal population [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical studies showed contradictory results. In one study, increased TPOAb positivity was detected [ 24 ], while increased autoimmunity was not detected in others [ 9 , 12 ]. In the light of this knowledge, we evaluated the TPOAb and TGAb in 205 patients, but we could not observe an increased rate of antibody positivity according to the normal population [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to controls COVID-19 patients displayed latent autoimmunity mediated by a higher frequency of autoantibodies, such as TPOAb, rheumatoid factor (RF), and antinuclear antibodies (ANAs), to mention a few. A meta-analysis of selected studies confirmed such an increased prevalence of autoantibodies in COVID-19 patients, being RF and ANAs the most common autoantibodies [ 80 ]. These findings suggest a role of SARS-CoV-2 infection in promoting/amplifying autoimmune disorders (AIDs) and support further post-COVID studies to evaluate the development of overt autoimmunity.…”
Section: Autoimmune Thyroid Disorders and Covid-19mentioning
confidence: 93%
“…The occurrence of autoimmune complications, including anti-phospholipid syndrome, autoimmune thrombocythemia, hemolytic anemia, Guillain-Barré, has been described in patients following SARS-CoV-2 infection [ 76–79 ]. Moreover, latent autoimmunity was checked by measuring a panel of rheumatic, thyroid, and phospholipid autoantibodies in sera samples from 120 hospitalized patients with COVID-19 in comparison to pre-pandemic samples from 100 healthy individuals [ 80 ]. Compared to controls COVID-19 patients displayed latent autoimmunity mediated by a higher frequency of autoantibodies, such as TPOAb, rheumatoid factor (RF), and antinuclear antibodies (ANAs), to mention a few.…”
Section: Autoimmune Thyroid Disorders and Covid-19mentioning
confidence: 99%
“…A final sample size of 33 patients was included for longitudinal autoantibody analyses and 12 were assessed for cytokines, lymphocyte populations and anti-SARS-CoV-2 antibodies (Figure 1A). Serological data of 100 patients, previously reported, served as historical control group for autoimmune comparisons [9], and a group of 8 pre-pandemic healthy individuals was the control group for the immunological assessment [8].…”
Section: Methodsmentioning
confidence: 99%
“…In case of ANAs positivity, anti-SSA/Ro, anti-SSB/La, anti-ribonucleoprotein (RNP) and anti-smith (Sm) antibodies were further evaluated by a commercial ELISA. All the assay kits were from Inova Diagnostics, Inc (San Diego, CA, USA) as previously reported [9]. Assessment of anti-IFN-α antibodies was done by ELISA (Thermo Fisher Scientific, Waltham, MA) following manufacturer's specifications.…”
Section: Autoantibodiesmentioning
confidence: 99%